2022
DOI: 10.3847/1538-4357/ac63a8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous View of FRB 180301 with FAST and NICER during a Bursting Phase

Abstract: FRB 180301 is one of the most actively repeating fast radio bursts (FRBs) that has shown polarization angle changes in its radio burst emission, an indication for their likely origin in the magnetosphere of a highly magnetized neutron star. We carried out a multiwavelength campaign with the FAST radio telescope and NICER X-ray observatory to investigate any possible X-ray emission temporally coincident with the bright radio bursts. The observations took place on 2021 March 4, 9 and 19. We detected five bright … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…These excursions reflect some combination of intrinsic variability and evolving properties of the depolarizing medium. A changing magnetoionic environment was recently proposed by Laha et al (2022) to explain the marginal linear polarization (<10%) observed from FRB 20180301A (Laha et al 2022), a source that has previously displayed significant linear polarization at similar frequencies (Luo et al 2020). Indeed, many of the L/I measurements reported here cover multiyear timescales.…”
Section: Depolarization Via Stochastic Faraday Rotationsupporting
confidence: 52%
“…These excursions reflect some combination of intrinsic variability and evolving properties of the depolarizing medium. A changing magnetoionic environment was recently proposed by Laha et al (2022) to explain the marginal linear polarization (<10%) observed from FRB 20180301A (Laha et al 2022), a source that has previously displayed significant linear polarization at similar frequencies (Luo et al 2020). Indeed, many of the L/I measurements reported here cover multiyear timescales.…”
Section: Depolarization Via Stochastic Faraday Rotationsupporting
confidence: 52%
“…The red data points correspond to our X-ray and radio fluence measurements from NICER, XMM-Newton, and Effelsberg observations of FRB 20200120E at the times of radio bursts B4 and B9. The black data points highlight X-ray and radio fluence measurements from observations of FRB 20180301A (luminosity distance of d L = 1.79 Gpc) with NICER and the Five-hundred-meter Aperture Spherical radio Telescope (FAST) [27] .…”
Section: Discussionmentioning
confidence: 99%
“…The radio bursts detected from FRB 20200120E can sometimes display multiple pulse components with extremely narrow component widths of ∼10-100 ns [23], [24] , making it the shortest duration radio emission observed from any FRB source to date. Simultaneous X-ray and radio observations of more distant FRB sources, located at luminosity distances farther than 100 Mpc, have been carried out in the past [25]- [27] , but the resulting upper limits have been unable to rule out most viable FRB progenitor models. These previous studies [25]- [27] have also not searched for prompt X-ray emission from FRBs on ultra-short timescales (≪ 1 ms) that are comparable to the widths of the radio bursts detected from FRB 20200120E.…”
mentioning
confidence: 99%
See 1 more Smart Citation